Quantitative Renal Echogenicity as a Tool for Diagnosis of Advanced Chronic Kidney Disease in Patients with Glomerulopathies and no Liver Disease - Alexandre B. Libório; Fernanda Macedo de Oliveira Neves; Candice Bezerra Torres de Melo; Tacyano Tavares Leite; Renata de Almeida Leitão (Karger Publishers, 2017)
Background/Aims: Glomerulopathy patients are prone to developing transitory reduced glomerular filtration rate (GFR), which can be difficult to differentiate from irreversible chronic kidney disease (CKD). Renal ultrasound can be useful, but differently from renal length, quantitative renal echogenicity has not been formerly evaluated regarding its capacity to identify irreversible advanced CKD. Methods: A prospective study was performed, where quantitative renal echogenicity was performed during renal biopsy in patients with suspected glomerular disease (n=197). Quantitative echogenicity was measured as the inverse of the ratio between the mean pixel densities of the renal cortex and adjacent liver using ScionImage software. Patients were followed during a six-months period to ascertain irreversible advanced CKD. Quantitative renal echogenicity and histopathology parameters discriminatory capacity were compared regarding their capacity to detect advanced and irreversible CKD - estimated GFR less than 30mL/min/1.73m2 confirmed after a six-month follow-up. Results: At renal biopsy, the mean eGFR was 53.9±33.6 mL/min/1.73m2 and 63 (32.0%) patients had an eGFR less than 30 mL/min/1.73m2. Mean kidney/liver echogenicity ratio was 1.06±0.19 and it was inversely correlated with eGFR at follow-up (r=-0.684, p<0.001). Multivariate analysis was performed to create a histopathology index that correctly identifies irreversible advanced CKD. Renal echogenicity discriminatory capacity to identify irreversible advanced CKD was 0.793 (0.719 -0.867), similar to the histopathology index. Elevated renal echogenicity with best discriminatory capacity was a kidney/liver ratio greater than 1.15. This cutoff had a predictive positive value of 92% in patients with eGFR less than 30mL/min/1.73m2. Conclusion: Quantitative renal echogenicity can be a useful tool in patients with glomerular disease and normal kidney size (>8cm) to identify those patients with irreversible advanced CKD.